Development of a Parent Training Module for Designing Adaptive Individualized Numeracy Learning Programs for Children Aged 5–6 Years - Fadhlia Nur Aini; Faisal Sundani Kamaludin; Achmad Ushuluddin (FKIP - Universitas Riau, 2026)
This study developed and evaluated an Adaptive Individualized Numeracy Learning Program training module for parents of children aged 5–6 years. A needs analysis involving focus group discussions and open-ended questionnaires revealed parents’ limited understanding of multidimensional numeracy concepts and individualized learning strategies, as well as the absence of structured guidance for home-based support. Using the ADDIE framework, the module was systematically designed, validated by experts, and implemented through small- and large-group trials. Findings indicated that the module met high standards of content and language feasibility and was practically applicable in home learning contexts. Effectiveness testing demonstrated a significant improvement in parents’ knowledge and readiness to design adaptive numeracy activities, with a very large effect size. Qualitative findings further showed enhanced parental confidence, improved ability to align activities with children’s developmental levels, and increased use of play-based strategies in daily routines. Overall, the module is pedagogically feasible and effective in strengthening parents’ capacity to support individualized early numeracy development at home.